ANALYSIS OF LESSON PLANS WRITTEN BY ENGLISH STUDENT-TEACHERS FOR YOUNG LEARNERS - Rahmawati Rahmawati; Zulhermindra Zulhermmida (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
This study is to describe the application of consistency principles in developing lesson plans of teaching English for young learners designed by student-teachers. The design of this research is descriptive quantitative. The instrument in this study is a checking guide sheet. The lesson plans, as data, were analyzed by comparing the consistency principles of developing lesson plan of teaching English for children with each document. Based on the analysis, there were 23 documents (38%) applying most of the principle of consistency within the development of the syllabus and only 1 document (2%) which does not apply any of the principles. In detail, 25 documents (42%) partially applied the principle of linkage and integration and no document (0%) which did not apply any of these principles. Then, 28 documents (47%) applied all of the principles of learning foreign languages for children and no document (0%) that did not apply any of the principle. Almost all documents (92% - 93%) implemented each principle of helping students’ development and practice language through collaboration, integrate language and content, and validate and integrating that learning with the learners’ language and culture. Next, most of documents (68% - 78%) applied the principles of providing an active and fun role in the learning experience, using multidimensional and thematic learning activities, validating and integrating the learning with language and culture of learners, and providing clear objectives and feedback on the language usage. In conclusion, the application of the principles of learning English for children lies in the range of 81%.